A pluralistic, socio-ecological approach to understand the long-term impact of mountain conservation: a counterfactual and place-based assessment of social, ecological and hydrological change in the Groot Winterhoek Mountains of the Cape Floristic Region - Holden, Petra Brigitte (Department of Biological Sciences, 2018)
The problem: For protected areas to remain relevant, we need to understand their impact on a wide set of conservation objectives and environmental outcomes. We also need to evaluate how this influence relates to the socio-ecological environment within which they occur. This is a complex endeavour requiring a pluralistic approach, which draws on a wide range of interdisciplinary fields. Research question: This thesis addresses the following question: What effects do mountain protected areas have on ecosystem services over time and how does this influence relate to broader socio-economic and ecological drivers of landscape change? Aim and objectives: I use a pluralistic, socio-ecological framing to assess the impact of ~40 years of mountain protection, drawing on comparisons of ~30 and ~40 years before and after protection respectively, with an adjacent area of similar terrain informing scenarios of counterfactual conditions. I also investigate what types of values (economic and intrinsic) are important when determining the impact of mountain protected areas. Thesis approach and methods: I operationalise the concepts of socio-ecological systems, ecosystem services, land use transitions and counterfactuals to investigate socio-ecological change and how it relates to protected area impact in the Groot Winterhoek, a mountain catchment in the south-western Cape of South Africa. This mountain catchment is important for regional water supplies for agricultural and domestic uses and falls in the Cape Floristic Region, a global biodiversity hotspot. It is comprised of privately owned mountain wildlands and a wilderness-protected area, known as the Groot Winterhoek Wilderness Area, established in 1978 (gazetted in 1985) which forms part of the Cape Floristic Region World Heritage Site. I combine methods from social science, ecology, environmental geography, geomatics and hydrology to understand the history of land use and cover (land use/cover) and associated ecosystem service trade-offs, how they are perceived by landowners as well as their wider impact on the region. Specifically, I assess the impact of protection on land use/cover, vegetation, fire and water flows over the last ~50 years, by comparing and contextualising results of change within the protected area to alternative scenarios of “no protection” (the counterfactual conditions). Vegetation and land use/cover change inside the protected area were determined respectively using 72 repeat terrestrial photographs and vegetation surveys, and an analysis of orthorectified aerial imagery. Methods used to construct the counterfactual scenarios of mechanisms (e.g. changes in land use/cover) that would likely drive vegetation changes inside the protected area included: i) 60 repeat surveys and in-depth interviews with landowners adjacent or proximal to the protected area owning unprotected land of similar terrain to the protected area; and ii) land use/cover change analysis of orthorectified aerial imagery of adjacent unprotected land of similar terrain before and after protected area establishment. 4 This latter information was used to understand the role of the protected area in driving vegetation changes inside the protected area. Social, biophysical and remote sensing results were directly used to parameterise land use/cover components of a hydrological model to determine the influence of protection on water flows. Specifically, water flows were simulated for the current state of the environment inside the protected area as well as for several counterfactual scenarios i.e. the alternative land use/cover scenarios of “no protection”. These counterfactual scenarios included land use/cover at two-time steps of ~30 and ~8 years before protection and one-time step ~40 years after protection both inside and outside the protected area. Results: Long-term change in ecosystem service use outside the protected area on privately owned land of similar terrain to inside the protected area (Section 3): Over the last ~50 years, outside the protected area, there was a shift from livestock-based, subsistence agriculture and small-scale farming to a diversified set of ecosystem service uses. The combined area of grazing and wildflower harvesting declined by 39%, while the number of landowners using the mountains for personal nature-based recreation and ecotourism increased by 61% and 23% respectively. Agriculture intensified in suitable areas of mountain land with the number of landowners cultivating land increasing by 20%. Exogenous socioeconomic drivers associated with globalisation and economic growth were important causal mechanisms of land use change. Landowners valued mountain protection for intrinsic and non-use reasons (73-80% of landowners), including existence, bequest and option values, as well as for the indirect use of water supply (72% of landowners) in comparison with direct use reasons such as spiritual/cultural experiences and nature-based recreation inside the protected area (18 and 50% of landowners respectively). Personal, nature-based recreation outside the wilderness-protected area was associated with valuing the protection of mountain land for intrinsic and non-use reasons. Long-term vegetation change inside the protected area and plausible mechanisms driving vegetation change (Section 4): Inside the mountain protected area, fynbos vegetation cover increased on average between 11 and 30% and there were significant declines in bare ground and rock cover. In 5 accumulation and fire intensities. However, these latter changes in land use/cover also occurred outside the protected area (see results summarised for Section 3 above and Section 4 below) and therefore cannot be attributed to protected area establishment. Land use/cover and the influence on water flows inside the protected area compared to counterfactual scenarios of no protection (Section 5): Declines in grazing and changes to the fire regimes occurred regardless of the protected area boundaries. In the past, there was a high frequency of small, low intensity fires across the landscape, both inside and outside the protected area. More recently, fires have been actively suppressed and this resultsin the build-up of biomass and the development of extensive, high intensity fires which, under suitable conditions, burn large expanses of the mountain catchment. Hydrological modelling showed that a high intensity burning regime negatively affected streamflow regardless of protected area boundaries. Streamflow increased by more than 80% under high flow conditions and decreased by more than 40% under low flow conditions relative to an unburnt ‘natural’ scenario. Over the last 50 years there has also been a substantial increase in dams, buildings and roads and minor increases in cultivation outside the protected area. This has been avoided inside the protected area where these land use/cover classes declined. If the increase in these land use/cover types observed outside the protected area occurred inside the protected area this would have resulted in reductions in daily streamflow leaving the protected portion of the catchment. For example, outside the protected area reductions of 8% to 25% of streamflow were observed during mid and low flow conditions respectively, particularly during dry years, in comparison to a ‘natural’ scenario. In contrast, inside the protected area streamflow recovered from past conditions to more closely resemble the natural flow conditions of the catchment. Therefore, had the protected area not been established there would have been losses in streamflow from the catchment as well as an increase in the degree of fragmentation within this mountain area. However, with increased water storage and fragmentation outside the protected area has also come increased socio-economic opportunities such as employment and local opportunities for ecotourism and sustainable agriculture e.g. indigenous cut flows. This highlights the importance of maintaining various forms of land management systems (multifunctional landscapes) within mountain ecosystems but also the need to understand the sustainability of different land management system types. Determining appropriate land management systems for mountain areas should be based on a full understanding of the impacts on ecosystem service benefits and costs at local and regional levels between social groups both spatially and temporally. Broader significance: This thesis contributes to the conservation literature on two main fronts. Firstly, it contributes conceptually and theoretically to understanding the dynamics of ecosystem services in relation to mountain protection. Secondly, it contributes methodologically by using an inclusive, trans- and interdisciplinary research approach for evidence-based conservation at a place-based and landscape level. The study provides a case 6 study example of the positive impact that mountain protection has on water-related ecosystem services, notably by maintaining streamflow throughout high to low flow periods and during dry years. It also provides clear evidence that ecosystem service trade-offs do not remain constant over time and shows that intrinsic and non-use values are required when describing the importance of mountain protected areas. In terms of understanding the impact that protected areas have in mountain regions, the research shows that complex processes are at play that extend beyond the boundaries of a specific protected area in both time and space. Interactions between global and local drivers were found to be prominent causal mechanisms of socio-ecological change and ultimately determined the influence of mountain-protection on land use/cover, fire, vegetation and water-related ecosystem services. The thesis emphasises that counterfactual framings are necessary to understand and attribute the impacts of protected areas on environmental outcomes, however pluralism and socio-ecological approaches are critical to determine plausible counterfactual conditions. This thesis focused only on landowners adjacent and proximal to the protected area owning the majority of mountain catchment land of similar terrain. It is likely that multiple socioeconomic trade-offs have occurred between different social groups and generations at both local and regional levels. Understanding how the disadvantages and benefits of the impacts of protected areas are apportioned across the landscape and temporally is an aspect that requires future research. Central to this would be to fully consider how human well-being is influenced both upstream and downstream, including at regional levels, and between social groups and across generations. Considering the impact of protected areas on the full range of ecosystem services and linking this to societal preferences and perceptions should be incorporated into the overall goal of developing an evidence base for conservation. This is because it is both scientific evidence and societal change that can determine protected area persistence and thus long-term protected area impact.